2007
DOI: 10.1159/000104472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-Fluorouracil and Mitomycin on the Healing of Intestinal Anastomosis

Abstract: Objective: Antineoplastic agents affect the healing of intestinal anastomosis. The aim was to evaluate the effect of 5-fluorouracil (5-FU) and mitomycin on the healing of the intestinal anastomosis and their schedule of administration. Material and Methods: Eighty-nine male albino Charles Foster rats with a mean weight of 256.57 g were divided into six groups. Group A represents the control, while in others varying schedules of chemotherapy (5-FU and mitomycin) were administered. The sacrifices were made on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
3

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
2
0
3
Order By: Relevance
“…Multiple studies have reported that chemotherapy administration impairs wound healing and that there is associated increase in wound complications in chemotherapy exposed patients [4,5]. The effects of HIPEC on wound healing are multiple (Figure 1): first HIPEC requires the concomitant use of chemotherapy and hyperthermia which are both known to increase cellular death and induce apoptosis [6,7]; second, tumor cytoreduction may require surgical resection of involved abdominal wall surfaces potentially compromising abdominal wall closure and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported that chemotherapy administration impairs wound healing and that there is associated increase in wound complications in chemotherapy exposed patients [4,5]. The effects of HIPEC on wound healing are multiple (Figure 1): first HIPEC requires the concomitant use of chemotherapy and hyperthermia which are both known to increase cellular death and induce apoptosis [6,7]; second, tumor cytoreduction may require surgical resection of involved abdominal wall surfaces potentially compromising abdominal wall closure and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical trauma-related proangiogenic plasma protein changes that persist for at least 3 weeks and immunosuppression likely account for some of these tumor stimulatory effects [6]. Presently, the initiation of adjuvant chemotherapy is delayed for 4-6 weeks after surgery because of fears that chemotherapy may impair wound and anastomotic healing [7][8][9][10]. Ideally what is needed are effective anticancer agents that do not inhibit wound healing and could be taken during the month after and, perhaps, the weeks before cancer resection.…”
mentioning
confidence: 99%
“…Οι Vasiliadis και συν 91 σε μία πειραματική μελέτη σε επίμυες βρήκαν ότι η συνδυασμένη χορήγηση 5-FU και λευκοβορίνης ελαττώνει τις πιέσεις διάσπασης των αναστομώσεων σε μέτρηση που έγινε την 8 η μετεγχειρητική ημέρα. Σε ανάλογη έρευνα των Shukla και συν239 οι πιέσεις διάσπασης ελαττώθηκαν μετά από χορήγηση συνδυασμού 5-FU και μιτομυκίνης. Στην δική μας μελέτη, η μέση τιμή πίεσης διάσπασης μετά από συνδυασμό χορήγησης 5-FU και ιρινοτεκάνης Έρευνα των Shukla και συν239 , που αφορούσε την επίδραση της 5-FU σε αναστομώσεις επίμυων, έδειξε αύξηση των συμφύσεων στην ομάδα που γινόταν ενδοπεριτοναϊκή χορήγηση 5-FU σε σχέση με την ομάδα ελέγχου, μετά από 7 ή 14 ημέρες χορήγησης.…”
unclassified
“…Σε ανάλογη έρευνα των Shukla και συν239 οι πιέσεις διάσπασης ελαττώθηκαν μετά από χορήγηση συνδυασμού 5-FU και μιτομυκίνης. Στην δική μας μελέτη, η μέση τιμή πίεσης διάσπασης μετά από συνδυασμό χορήγησης 5-FU και ιρινοτεκάνης Έρευνα των Shukla και συν239 , που αφορούσε την επίδραση της 5-FU σε αναστομώσεις επίμυων, έδειξε αύξηση των συμφύσεων στην ομάδα που γινόταν ενδοπεριτοναϊκή χορήγηση 5-FU σε σχέση με την ομάδα ελέγχου, μετά από 7 ή 14 ημέρες χορήγησης. Ανάλογα αποτελέσματα έδειξαν και έρευνες των Kanellos και συν 9,89.…”
unclassified